Partial nephrectomy for renal cell carcinoma. A population-based study on kidney function following nephrectomy - Elín Maríusdóttir 1984- (2013)
Introduction: The aim of this retrospective study was to compare renal function in a population-based cohort of renal cell carcinoma (RCC) patients who underwent partial (PN) or radical nephrectomy (RN). Materials and methods: Forty-four consecutive RCC patients (mean age 60 years, 64% male) who underwent PN in Iceland between 2000 and 2010 were compared with 44 TNM-matched controls (mean age 65 years, 52% male) who underwent RN during the same period. Estimated glomerular filtration rate (eGFR) and survival were calculated, and predictors of chronic kidney disease (CKD) were evaluated with multivariate analysis. Results: In 16 cases (36%), PN was performed for imperative reasons (single kidney, reduced kidney function, or bilateral kidney tumours) but 28 patients had a normal contralateral kidney. The groups were similar regarding preoperative eGFR, median follow-up, and TNM stage, but age and ASA score were significantly higher in the RN group. Six months after surgery, eGFR was significantly higher in the PN group. By multivariate analysis, RN contributed negatively to eGFR six months after surgery (-12.6 mL/1.73 m2, p <0.001) and increased the risk of new-onset chronic kidney disease (CKD) compared to PN (OR=3.07, 95% CI: 1.03–9.79, p=0.04). At a median follow-up of 44 months, no patients in either group had a recurrence of RCC. The 5-year overall survival (Kaplan-Meier) was 100% in the PN group and 65% in the RN group (log-rank test, p <0.001). Conclusion: eGFR was significantly lower after RN, and these patients were three times more likely to develop new-onset CKD. Our findings suggest that PN successfully preserves kidney function compared to RN with good oncological outcome and survival.